2012
DOI: 10.1007/s00415-011-6389-y
|View full text |Cite
|
Sign up to set email alerts
|

Semantic dementia associated with corticobasal syndrome: a further variant of frontotemporal lobe degeneration?

Abstract: The traditional clinical picture of corticobasal syndrome (CBS) is of a subcortical syndrome of akinesia and rigidity, combined with cortical features of limb apraxia and cortical sensory loss [1,2].In recent years, patients with 'cortical' deficits other than limb apraxia have been described, allowing delineation of ' cognitive' subtypes of CBS [3][4][5][6][7]. In particular, an association has been recognised between CBS and progressive nonfluent aphasia.The association between 'pure' semantic dementia and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Our patient's language was marked by confrontation naming deficits, corroborated by the very low BNT score and by our locally developed naming test. Moreover, his pattern of performance has been reported in a similar patient with SD and CBS (Luzzi et al, 2012). His score (25/40, 62%) was identical to our patient's on a locally developed picture naming test, and remained stable 2 years later (24/40).…”
Section: Neuronal Loss and Gliosissupporting
confidence: 75%
See 2 more Smart Citations
“…Our patient's language was marked by confrontation naming deficits, corroborated by the very low BNT score and by our locally developed naming test. Moreover, his pattern of performance has been reported in a similar patient with SD and CBS (Luzzi et al, 2012). His score (25/40, 62%) was identical to our patient's on a locally developed picture naming test, and remained stable 2 years later (24/40).…”
Section: Neuronal Loss and Gliosissupporting
confidence: 75%
“…Consistent with these findings is the known association of CBD with the other two clinical FTLD syndromes, progressive nonfluent aphasia and a behavioral variant of frontotemporal dementia (Kertesz et al, 2007;Kouri, Whitwell, Josephs, Rademakers, & Dickson, 2011;Murray et al, 2007;Rabinovici & Miller, 2010). Frontal behavioral manifestations are present in four of the reported SD-CBD cases (Ikeda et al, 1996;Mathuranath et al, 2000;McMonagle et al, 2006;Raggi et al, 2007), while abnormal performances on executive testing are reported in the fifth one (Luzzi et al, 2012). Our patient's language was marked by confrontation naming deficits, corroborated by the very low BNT score and by our locally developed naming test.…”
Section: Neuronal Loss and Gliosismentioning
confidence: 49%
See 1 more Smart Citation